Joint involvement in canine visceral leishmaniasis: Orthopedic physical examination, radiographic and computed tomographic findings - Silva, Alexandre Redson S.; Oliveira, Hugo S. [UNESP]; Gomes, Ana Amélia D.; Beserra, Hugo Enrique O. [UNESP]; Silva, Jeana P. [UNESP]; Santos-Doni, Thaís R.; Tsunemi, Miriam H. [UNESP]; Marcondes, Mary [UNESP]; Rahal, Sheila C. [UNESP]; Mamprim, Maria J. [UNESP] (Elsevier, 2021)
This study aimed to evaluate the joint involvement in dogs with visceral leishmaniasis by means of orthopedic physical examination, radiographic and computed tomographic (CT) findings. Of the 46 evaluated dogs, an overall of 91.3 % presented joint (carpal, tarsal, elbows, and stifle) abnormalities, observed on physical examination, radiography and/or CT. In 67.3 % of the dogs orthopedic examination showed no abnormalities. Among the 31 dogs with normal orthopedic examination, 61.3 % showed radiographic and CT findings suggestive of osteoarthritis, 25.8 % presented normal radiographs with abnormalities evidenced only on CT, while 12.9 % presented normal radiographs and CT imaging. From the 15 dogs with abnormal orthopedic examination, 80 % had abnormal radiographic and CT findings suggestive of osteoarthritis, while 20 % presented normal radiographs with abnormalities evidenced only in their CT. Radiographic and CT findings included evident trabecular pattern, subchondral bone sclerosis, osteolysis, mixed bone lesions (osteolytic–proliferative lesions), soft tissue swelling around the joint (edema), joint space narrowing, bone proliferation, osteophytes, bone cyst and cartilage flap. Based on CT results the most affected joints, among those assessed, were the tarsal (80.9 %), followed by stifle (78.5 %), carpal (64.2 %), and elbows (54.7 %). Except by one dog that presented only one stifle joint compromised, the other three joints presented bilateral abnormalities in all dogs.
Keywords: Arthritis; Diagnosis; Dog; Lameness; Leishmaniasis; Polyarthritis